Pemberian Senam Ergonomis untuk Penurunan Nyeri Dismenorhea pada Wanita Usia Subur (WUS) - Prihandhani, I Gusti Agung Ayu Sherlyna; Trisna, Made Oktaviani Bulan (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the effect of providing ergonomic exercises on reducing dysmenorrhea pain in women of childbearing age. The method used is a one-group pre-test and post-test design. The Paired T-Test research showed a result of 3.179 with a P-value of 0.000 < (0.05). In conclusion, there is an influence of ergonomic exercise on reducing dysmenorrhea pain in women of childbearing age. Keywords: Dysmenorrhea Pain, Ergonomic Exercises, Women of Childbearing Age